2015
DOI: 10.1515/rela-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Speech Melody Properties in English, Czech and Czech English: Reference and Interference

Abstract: Two major objectives were set for the present study: to provide reference data for the description of Czech and English F0 contours, and to investigate the limits of the ‘interference hypothesis’ on Czech English data. Altogether, the production of 40 speakers in 2392 breath-group F0 contours was analyzed. The speech of 32 professional speakers of English and Czech provides reference values for various acoustic correlates of pitch level, pitch span and downtrend gradient. These values were subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…While the segmental determiners and prosodic correlates of lexical stress and the related phenomena of phrasing and rhythm have been intensively analyzed for Czech in the last decades (Janota, 1967;Janota and Palková, 1974;Dankovičová, 2001;Volín, 2008a;Volín and Weingartová, 2012), only little is known about the use of intonation and emphasis patterns in Czech. In fact, research on the prosody of emphatic expressions in Czech hardly exists (but see e.g., Jančák, 1957).…”
Section: State Of the Art In Czech Prosody Researchmentioning
confidence: 99%
“…While the segmental determiners and prosodic correlates of lexical stress and the related phenomena of phrasing and rhythm have been intensively analyzed for Czech in the last decades (Janota, 1967;Janota and Palková, 1974;Dankovičová, 2001;Volín, 2008a;Volín and Weingartová, 2012), only little is known about the use of intonation and emphasis patterns in Czech. In fact, research on the prosody of emphatic expressions in Czech hardly exists (but see e.g., Jančák, 1957).…”
Section: State Of the Art In Czech Prosody Researchmentioning
confidence: 99%
“…As shown in Figure 12, our speakers' pitch range, as evidenced by the 80-percentile range, was confirmed to be quite narrow; the only exception is speaker S10, whose intonation indeed strikes listeners as remarkably lively. Volín et al (2015) reported their Czech English speakers' 80-percentile range around 4 semitones (ST), and we can see that the median value of most of the speakers in this study moves around the same value, with three speakers' median even below 3 ST.…”
Section: Melodic Patterningmentioning
confidence: 50%
“…While the pitch range of native British speakers was similar to that of the British newsreaders, it was by over 1 semitone narrower in the L2 speakers of English than in the L1 Czech newsreaders. The results of the study by Volín et al (2015) therefore do not support a straightforward transfer hypothesis, according to which one would predict values intermediate between (or identical to) those of Czech and English. With the pitch range in English as an L2 of Czech speakers even narrower than in L1 Czech, the authors suggest that there must be other factors at play, such as anxiety of the L2 speakers.…”
Section: Intonation In Czech Englishmentioning
confidence: 56%
See 1 more Smart Citation
“…For example, see the reference values that are reported in Andreeva et al (2014), Pépiot (2014), and Volín et al (2015). Moreover, the sweet spots are limited at both ends.…”
Section: How Prosodic Features Are Correlated With Speaker Charismamentioning
confidence: 79%